Efficacy of Orlistat on Hyperbilirubinemia in Full Term Neonates - M Habibi; E Bahadoran; F SamieeRad; A Javadi; G Roozbehani (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2024)
Background and Objective: Jaundice is common in infants and occurs because of hyperbilirubinemia, which can lead to brain injury in neonates. Phototherapy, in addition to its serious side effects, does not seem to be enough in resolving jaundice. This clinical trial aims to compare the efficacy of orlistat and phototherapy combination therapy with that of phototherapy alone in the treatment of neonatal jaundice. Methods: This clinical trial was performed on 120 term neonates with jaundice. Block randomization was used to allocate the infants to the intervention and control groups. The intervention group received orlistat (4 mg/kg body weight) for three consecutive oral doses at the first, second and third day of hospitalization, along with phototherapy. The control group received a placebo and phototherapy. Total and direct plasma bilirubin levels were measured at baseline (before intervention) as well as 24 and 72 h after treatment. Findings: There were no statistically significant differences between the two groups in terms of infant sex, weight, or age. The mean total and direct bilirubin levels in the experimental group did not change compared to those in the control group at the end of the trial (10.44±1.35 vs. 10.6±2.8 and 0.4±0.1 vs. 0.5±0.1, respectively). Conclusion: Orlistat appears to be ineffective in accelerating bilirubin reduction in neonates with jaundice, at least for the first three days of life.